Perilaku Cyberslacking dan Prokrastinasi Akademik Pada Mahasiswa Universitas Syiah Kuala - Sulha, Khalila; Yulandari, Nucke; Iskandar, Iskandar; Faradina, Syarifah (Syiah Kuala Psychology Journal, 2025)
University Students are often faced with various academic demands that require good time management and discipline. However, many of them tend to engage in academic procrastination, which is the habit of delaying tasks or academic responsibilities. One factor that can influence this behavior is cyberslacking, which refers to the use of the internet for non-academic activities during study time. In the digital era, easy access to the internet often tempts students to divert their attention to social media, entertainment, or other activities that reduce academic productivity. The purpose of this study is to examine the relationship between cyberslacking and academic procrastination among students at Syiah Kuala University. This study involved 340 students at USK who were selected using simple random sampling techniques. The measurement tools used in this study were the Academic Procrastination Scale developed by McCloskey and Scielzo (2015) and the Cyberslacking Scale developed by Akbulut (2016). The results of this study indicate a significant relationship between cyberslacking and academic procrastination among students at Syiah Kuala University, with a significant value of p 0.001 (r = 0.181). This means that the higher the level of cyberslacking performed by students, the higher their level of academic procrastination, and vice versa.Mahasiswa kerap dihadapkan pada berbagai tuntutan akademik seperti manajemen waktu dan disiplin yang baik. Namun, banyak di antara mereka cenderung melakukan prokrastinasi akademik, yaitu kebiasaan menunda pengerjaan tugas atau kewajiban akademik. Salah satu faktor yang dapat memengaruhi perilaku ini adalah cyberslacking, yaitu penggunaan internet untuk kegiatan non-akademik selama waktu belajar. Dalam era digital, kemudahan akses internet sering kali membuat mahasiswa tergoda untuk mengalihkan perhatian mereka ke media sosial, hiburan, atau aktivitas lainnya yang mengurangi produktivitas akademik. Tujuan dari penelitian ini adalah untuk mengetahui hubungan perilaku cyberslackling dengan prokrastinasi akademik pada mahasiswa Universitas Syiah Kuala. Penelitian ini melibatkan 340 mahasiswa di USK yang dipilih melalui teknik simple random sampling. Alat ukur yang digunakan dalam penelitian ini Academic Procrastination Scale yang disusun oleh McCloskey dan Scielzo (2015) dan Cyberslacking Scale yang dikembangkan oleh Akbulut (2016). Hasil penelitian ini menunjukkan bahwa terdapat adanya hubungan antara perilaku cyberslacking dengan prokrastinasi akademik pada mahasiswa Universitas Syiah Kuala dengan nilai signifikansi p=0,001 (r=0.181) artinya, semakin tinggi cyberslacking yang dilakukan mahasiswa, maka semakin tinggi juga perilaku prokrastinasi pada mahasiswa, begitu pula sebaliknya.